2021
DOI: 10.3389/fimmu.2021.628654
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0088194 Promotes the Invasion and Migration of Rheumatoid Arthritis Fibroblast-Like Synoviocytes via the miR-766-3p/MMP2 Axis

Abstract: Dysregulation of circular RNAs (circRNAs) is involved in various human diseases. Fibroblast-like synoviocytes (FLSs), which form the lining of the joint, are epigenetically imprinted with an aggressive phenotype and contribute to joint destruction in rheumatoid arthritis (RA). In the present study, we identified a novel circRNA, Circ_0088194, which was upregulated in RA fibroblast-like synoviocytes (RA-FLSs) and correlated with the disease activity score in 28 joints. Overexpression of Circ_0088194 promoted RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Therefore, the multi-functionality of circRNAs makes them ideal for researching and predicting disease. In recent years, increasing numbers of studies have shown that the abnormal expression of circRNAs is closely related to the development of a variety of rheumatisms, such as systemic lupus erythematosus ( Wang X. et al, 2021 ), rheumatoid arthritis ( Cai et al, 2021 ), and osteoarthritis ( Liu et al, 2021 ), etc., However, the role of circRNAs in gout is not well understood. In this study, genome-wide microarrays were used to analyze the circRNA expression profile in the PBMCs of gout patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the multi-functionality of circRNAs makes them ideal for researching and predicting disease. In recent years, increasing numbers of studies have shown that the abnormal expression of circRNAs is closely related to the development of a variety of rheumatisms, such as systemic lupus erythematosus ( Wang X. et al, 2021 ), rheumatoid arthritis ( Cai et al, 2021 ), and osteoarthritis ( Liu et al, 2021 ), etc., However, the role of circRNAs in gout is not well understood. In this study, genome-wide microarrays were used to analyze the circRNA expression profile in the PBMCs of gout patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al identified that circ_0088194 was up-regulated in RA FLS; it could act as miR-766-3p sponge and promote the expression of downstream target gene MMP2, thereby facilitating the fibroblast−like synoviocytes' invasion and migration. It may be a novel and promising target for RA (167). Qu et al suggested that circ-AFF2 was up-regulated in synovial tissues and FLS of RA; circ-AFF2 could bind to the miRNA miR-650; it enhances the expression level of downstream target 2',3'-cyclic nucleotide phosphodiesterase (CNP) and promotes fibroblast−like synoviocyte proliferation, inflammatory response, migration, and invasion (168).…”
Section: Circrnas and Ramentioning
confidence: 99%
“…It is a single-stranded covalently closed circular transcripts which make it more stable and harder to degrade in cells [9]. Recently, circRNAs have been confirmed as diagnostic biomarkers of many diseases like cardiovascular diseases, rheumatoid arthritis, kidney disease, and cancer [10][11][12][13]. Nowadays, the underlying mechanism of circRNA function significantly lies in the miRNA or protein sponges, enhancer of protein function, protein scaffolding, protein recruitment, and templates for peptides translation [9].…”
Section: Introductionmentioning
confidence: 99%